Efeitos das desintegrinas Alternagina-C e DisBa-01 de Bothrops alternatus em fibroblastos, células endoteliais e tumorais - Ribeiro, Juliana Uema (Universidade Federal de São Carlos, 2009)
Disintegrins are small cysteine-rich proteins with an RGD motif isolated from viperidae snake venoms. DisBa-01, a recombinant RGD-disintegrin from Bothrops alternatus snake venom, inhibits melanoma cell metastasis and also platelet aggregation in murine models by interactions with β3 integrin cell receptors. Also, this RGD-disintegrin inhibits human microvascular endothelial cell (HMEC-1) proliferation in vitro and angiogenesis in vivo. Alternagin-C (ALT-C), a disintegrin-like protein from Bothrops alternatus, is a potent inhibitor of the collagen binding to α2β1 integrin which plays an essential role in the adhesion of normal and tumor cells to the extracellular matrix. Also, this protein can modulate angiogenesis where low concentrations of ALT-C positively regulate the formation of new blood vessels, whereas high ALT-C concentrations negatively modulates this process. This work presents the effects of DisBa-01 and ALT-C: 1) on the adhesion of breast cancer invasive MDA-MB-231 cells to the ECM proteins and to the subendothelial matrix produced by HUVEC (human vascular endothelial cells) under static and dynamic conditions; and 2) on the VEGFRs expression on endothealial cells. ALT-C inhibited tumoral cell adeshion to almost ECM proteins individually and also to ECM. Only 10000nM ALT-C inhibited tumoral cell adhesion to the HUVEC matrix under static conditions. Under flow, tumoral adhesion were inhibited by 100nM and 1.000nM ALT-C. Flow induces α2β1 activation in endothelial cells and MDA-MB- 231 cells expressed high levels of α2β1. Thus, a possible activation of this integrin by the shear stress could enhance its interactions with ALT-C. DisBa-01 had no effect on the tumoral cell adhesion to HUVEC matrix under static conditions. On the other hand, under flow the RGD-disintegrin strongly inhibited tumoral and platelet adhesion. Thus, a possible activation of αVβ3 by flow could enhance its interactions with DisBa-01. About VEGFR expression, DisBa-01 down-regulated VEGFR-1 and VEGFR-2 expression in almost all tested concentrations. ALT-C up-regulates VEGFR-2 expression at lower concentration. These results can explain at least in part the effects of DisBa-01 and ALT-C in angiogenesis. The anti-adhesives and antiangiogenics ALT-C and DisBa-01 properties may be helpful for the study of tumoral metastasis as well as in the design of new therapeutic agents targeting tumor cell adhesion on extravasation and invasion steps.
Keywords: Biologia celular; Desintegrinas; Células - adesão; Neovascularização; VEGF (Fator de Crescimento de Endotélio Vascular); Expressão gênica; CIENCIAS BIOLOGICAS::GENETICA